Wesley Clair Mitchell (1874-1948) - Schumpeter, Joseph A. (Quarterly Journal of Economics, 1950)
Introduction, 139. — I. The formative period, 140. — II. Views on policy, ideology, and theory, 142. — III. Business Cycles, 1913, 146. — IV. The National Bureau and Measuring Business Cycles, 151.